Traditional Paintings on the Skin of the ASEI Papuan Community - Wenda, Nias; Sinaga, Osberth (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
As technological advancements continue to progress, customs and values have undergone significant shifts. However, the passion of the younger generation, particularly Papuan children and those residing in Sentani Village Asei, for Sentani paintings on kombouw bark is beginning to wane. These developments and increasingly advanced technological advancements have not only led to the shifting of traditions and values, but also the erosion of the love for young generations, especially Papuan children and those in Sentani Village Asei, for the art of painting Sentani motifs on kombouw bark. This phenomenon suggests that a substantial portion of school-aged Sentani children lack knowledge or understanding of the Sentani motifs themselves. The purpose of this research is to delve into the function and significance of traditional kombouw bark painting within the Asei community of Sentani District, Papua. This research employs a qualitative approach, utilizing ethnographic methods, to explore the values, functions, and meanings of traditional paintings on kombouw bark within society. The findings reveal that kombouw paintings serve multiple purposes, including ritual, spiritual, social, economic, and aesthetic functions. Each motif carries a profound symbolic meaning that encapsulates the relationship between individuals and nature, spirituality, and philosophical beliefs. Furthermore, this study identifies conservation efforts undertaken through the role of Traditional Institutions, artists, and development strategies aimed at preserving cultural heritage. This conclusion underscores the paramount importance of kombouw painting as a sustainable expression of Asei cultural identity. Conservation efforts for Kombouw Painting involve Traditional Institutions, who are responsible for maintaining, protecting, and preserving this painting art. This includes ensuring the authenticity of traditional motifs.